Discourse in the history and the legitimation mechanisms - Parada Ulloa, Marcos (2016)
The purpose of this paper is to reflect on the relationship between the historical discourse and its legitimation mechanisms. It also seeks to understand the guidelines for historical processes and the influence of dominant groups or sectors within society that result in a struggle between dominated and dominators, leading to develop legitimating mechanisms